The influence of job stress on teachers' job satisfaction in government aided Islamic secondary schools in Selangor / Husna Al-Amani Samsudin - Samsudin, Husna Al-Amani (2012)
The purpose of this research was to examine the influence of teachers’ job stress on their job satisfaction among the Government Aided Islamic Secondary School teachers in Selangor. In addition, the research was aimed to investigate to what extent the school teachers are under stress or satisfied in their work, to identify the factors underlying the sources of job stress and to examine the differences in the level of job stress and job satisfaction for different demographic variables. The study was conducted using mixed-methods research where both survey and structured interview were implemented. 111 respondents took part in the survey and nine teachers were interviewed. The findings indicated that the level of job stress among the teachers in general was at the medium level with relationship at work and job intrinsic factors as the most dominant factors in influencing their level of stress, and there was no significant difference in the level of job stress for different demographic variables of gender, age group and positions held. The overall level of their job satisfaction was at the medium level. The male teachers were reported to significantly experience higher job satisfaction than the female teachers but no significant difference in the level of job satisfaction was reported for the other two variables. The level of job stress experienced by the teachers has a significantly negative relationship with teachers’ job satisfaction (r = -.332, p-value = .000) where teachers felt unhappy and unmotivated towards their job to the extent that they wanted to opt for early retirement or pursuing other careers. The findings are hoped will contribute to the general knowledge and understanding on teachers’ job stress and how it influences their job satisfaction, and benefit the teachers, school administrators and the State Education Department in curbing the problems from becoming worse.